The relationships between supplier development, commitment, social capital accumulation and performance improvement - Krause, Daniel R.; Handfield, Robert B.; Tyler, Beverly B. (Journal of Operations Management, 2007)
Abstract This study investigates the relationships between U.S. buying firms’ supplier development efforts, commitment, social capital accumulation with key suppliers, and buying firm performance. We identify linkages between supply chain management research on supplier development and organization theory research on social capital to consider how buying firm commitment to a long‐term relationship, cognitive capital (goals and values), structural capital (information sharing, supplier evaluation, supplier development), and relational capital (length of relationship, buyer dependency, supplier dependency) are related to buying firm performance improvements (cost improvements, and quality, delivery, flexibility improvements). Analysis of buying firms from the U.S. automotive and electronics industries provides support for the theory that buyer commitment and social capital accumulation with key suppliers can improve buying company performance. Moreover, the findings suggest that the relationships of structural and relational capital vary depending on the type of performance improvement considered.